Clinical Spectrum of Pregnancy Related Dermatoses in a Tertiary Care Hospital in Western India - Pooja Agarwal; Sneha V Chaudhari; Ashish Jagati; Santoshdev P Rathod; Sabha Talib Neazee (Medsci Publications, 2020)
Introduction: Pregnancy is characterized by altered endocrine, metabolic, and immunologic milieus resulting in multiple cutaneous changes, both physiologic and pathologic. This research was undertaken to study physiological changes of pregnancy and prevalence of various pregnancy specific and non-specific dermatoses. Methodology: A retrospective study was conducted at the dermatology out-patient department of a tertiary care center in western India and data of 308 pregnant patients presenting with dermatoses, in the age-group of 19-35 years was analyzed. Detailed history, clinical examination and necessary investigations were reviewed. Results: Among 308 patients, 302(98.05%) presented with physiological skin changes of pregnancy, 118(38.31%) had pregnancy specific and 185(60.06%) had pregnancy non-specific dermatoses. The most common physiological change was pigmentary changes (n=294). Atopic eruption of pregnancy (n=79) was the most common pregnancy specific dermatoses followed by polymorphic eruption of pregnancy (n=38). In non-specific dermatoses, infectious diseases were more common (fungal, n=128; viral, n=25). Conclusion: Pregnancy non-specific dermatoses were seen more commonly than pregnancy specific dermatoses. Lower socioeconomic strata and overcrowding may be the reasons behind large number of infectious dermatoses that we saw in our study.